Les Principes De Jogjakarta: Principes sur l'application de la législation internationale des droits humains en matière dórientation sexuelle et d'identité de genre (2006)
Principes additionnels et obligations additionnelles des états au sujet de l’application du droit international des droits humains en matière d’orientation sexuelle, d’identité de genre, d’expression de genre et de caractéristiques sexuelles pour completer les Principes de Jogjakarta Depuis leur adoption en 2006, les Principes de Jogjakarta ont évolué pour devenir une déclaration faisant autorité sur les droits humains des personnes « d’orientations sexuelles et d’identités de genre diverses ». La dernière décennie a été témoin de développements significatifs dans le domaine du droit international des droits humains, ainsi que dans la compréhension des violations des droits humains subies par les personnes « d’orientations sexuelles et d’identités de genre diverses », et dans la reconnaissance des violations souvent distinctes touchant des personnes en raison de leur « expression de genre » ou de leurs « caractéristiques sexuelles ».Les Principes de Jogjakarta plus 10 (PJ+10) visent à documenter et à détailler ces développements à travers un ensemble de Principes additionnels et d’Obligations additionnelles des États.
https://yogyakartaprinciples.org/principles-fr/
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; antiracisme; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; outils; pol4022; premier cycle; périodes historiques; queer; racisme; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Comment devient-on homo ou hétéro? - Clerget, Stéphane (JC Lattès, 2006)
Le pédopsychiatre présente les découvertes récentes de la psychanalyse, la neurobiologie, la génétique, l'histoire, la sociologie, etc., à propos de la construction de l'identité sexuelle et de la part d'inné et d'acquis dans la définition des préférences sexuelles.
Section: 428 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

Sex objects: art and the dialectics of desire - Doyle, Jennifer (University of Minnesota Press, 2006)
The declaration that a work of art is “about sex” is often announced to the public as a scandal after which there is nothing else to say about the work or the artist-controversy concludes a conversation when instead it should begin a new one. Moving beyond debates about pornography and censorship, Jennifer Doyle shows us that sex in art is as diverse as sex in everyday life: exciting, ordinary, emotional, traumatic, embarrassing, funny, even profoundly boring. Sex Objects examines the reception and frequent misunderstanding of highly sexualized images, words, and performances. In chapters on the “boring parts” of Moby-Dick, the scandals that dogged the painter Thomas Eakins, the role of women in Andy Warhol's Factory films, “bad sex” and Tracey Emin's crudely evocative line drawings, and L.A. artist Vaginal Davis's pornographic parodies of Vanessa Beecroft's performances, Sex Objects challenges simplistic readings of sexualized art and instead investigates what such works can tell us about the nature of desire. In Sex Objects, Doyle offers a creative and original exploration of how and where art and sex connect, arguing that to proclaim a piece of art “about sex” reveals surprisingly little about the work, the artist, or the spectator. Deftly interweaving anecdotal and personal writing with critical, feminist, and queer theory, she reimagines the relationship between sex and art in order to better understand how the two meet-and why it matters.
OCLC: ocm61879732
Keywords: approches et analyses; art contemporain; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; premier cycle; queer; sexualité; thématiques

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis